A review of detection plagiarism in indonesian language - Widaningrum, Ida; Mustikasari, Dyah; Arifin, Rizal; Sugianti, Sugianti (Research and Social Study Institute (ReSSI), 2018)
Plagiarism is the act of copying the work of another person in the form of writing, ideas, creative ideas or other without including the source of the work or idea. This action is of course very disrespectful, violates the code of ethics and is opposed by all parties, both by scientists and the government. This happens because the use of the internet provides unlimited information services. Many studies have been carried out, raising the theme of this plagiarism. This article will review how far the plagiarism research has been done on Indonesian writing. By knowing the development of plagiarism research, further research will have better sustainability.